2021
DOI: 10.1186/s12882-021-02582-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-CoV-2 antibodies in hemodialysis patients in Senegal: a multicenter cross-sectional study

Abstract: Background Hemodialysis patients are among high-risk groups for COVID-19. Africa is the continent with the lowest number of cases in the general population but we have little information about the disease burden in dialysis patients. Objectives This study aimed to describe the seroprevalence of SARS-CoV-2 antibodies in the hemodialysis population of Senegal. Patients and methods We conducted a multicen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The men were predominant in our cohort as what was found in a previous study measuring COVID-19 seroprevalence among Senegalese hemodialysis patients [19]. Several studies evaluating the SARS-CoV-2 vaccine response in dialysis patients described a male predominance and its association with the vaccinal response [20] [21].…”
Section: Discussionsupporting
confidence: 71%
“…The men were predominant in our cohort as what was found in a previous study measuring COVID-19 seroprevalence among Senegalese hemodialysis patients [19]. Several studies evaluating the SARS-CoV-2 vaccine response in dialysis patients described a male predominance and its association with the vaccinal response [20] [21].…”
Section: Discussionsupporting
confidence: 71%
“…The first seroprevalence surveys carried out in Senegal were conducted in 2020 after the first wave and showed a lower seroprevalence of around 20%. Between June and September 2020, Seck et al found a SARS-CoV-2 seroprevalence rate of 21.1% (95% CI = 16.7–26.1%) [37]. During the same period, Ahouidi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they often experience an asymptomatic or mild SARS-CoV-2 infection associated with lower serum titers [49]. In Senegal, during the first wave, it was reported that seroprevalence of SARS-CoV-2 was higher in patients older than 65 years [37].…”
Section: 6%mentioning
confidence: 99%
“…However, high quality, representative studies in Africa continue to be rare. Studies tend to rely on opportunistic data collection, such as from blood donors [14][15][16][17][18][19], healthcare workers [20][21][22][23][24][25], or patients coming to health facilities for reasons other than COVID-19 [26][27][28][29][30][31], none of which are demographically representative of the general population. In addition, where population-representative seroprevalence studies do exist, they tend to be conducted in national capitals or large cities, and the majority have a moderate to high risk of bias (e.g.…”
Section: Introductionmentioning
confidence: 99%